Dynamic Effects of Corruption on General Government Final Consumption Expenditure: Evidence from OECD Countries - Aktaş, Emin Efecan (Public Finance Quarterly, 2021)
The relationship of corruption with macroeconomic indicators and its widespread negative impact over the years has been the subject of many empirical studies. Public expenditures, which are among these macroeconomic indicators, are one of the fiscal policy tools and their size and amount can be alternated by policymakers who gain an advantage from corruption. In this respect, the effect of corruption on the government final consumption expenditure is interrogated by System Generalized Methods of Moment panel data analysis in this study. Using four different corruption indexes in terms of robustness check, and forecasting covering the 2002–2018 period for 37 OECD countries proclaim that the corruption indexes in 3 models are significantly and positively related to public expenditures, while the other corruption index is positively but insignificantly correlated.